High Deterrence Capacity and Maritime Oriented Defense Transformation Towards a Golden Indonesia 2045 - Ahmad Fanani; I Wayan Midhio; Afrizal Hendra (PT FORMOSA CENDEKIA GLOBAL, 2024)
As the largest archipelagic country in the world, Indonesia consists of more than 17,000 islands with a coastline of 108,000 km, making it one of the countries with the largest maritime area. With a strategic position between two oceans (the Indian and the Pacific) and two continents (Asia and Australia). In realizing the big vision for Golden Indonesia 2045, one of them is having a strong defense needed to face increasingly complex global challenges. The research method used is a literature study involving analysis of documents, books, journal articles and information from official websites. Furthermore, the study results show Countries that have high technology in defense systems such as advanced radar systems, submarines and drones can increase the effectiveness and deterrence of maritime defense systems. Apart from that, joint military exercises and cross-field operations can increase naval readiness and operational capabilities, Defense Diplomacy and Regional Cooperation can also help build alliances and increase deterrence and lastly, Human Resource Capacity Development can help in achieving success. operating a sophisticated maritime defense system relies heavily on the capabilities of military personnel